9. Commissioning of the first synchrotron-based scanning proton beamline for ocular melanoma treatments. (December 2018) - Mastella, E.; Magro, G.; Mirandola, A.; Molinelli, S.; Russo, S.; Vai, A.; Maestri, D.; Mairani, A.; Fiore, M.R.; Mosci, C.; Valvo, F.; Orecchia, R.; et al.
Abstract : Purpose: Around 10 centers worldwide treat ocular tumors with proton therapy, all with dedicated eyelines. Our synchrotron-based facility is equipped with general-purpose fixed beamlines; proton and carbon ion treatments are delivered with pencil beam scanning modality (range in water 3 ÷ 32 cm). Recently, our proton beamline was adapted to treat also ocular diseases. The main dosimetric properties of this new eyeline are described in this work. Methods: A 3 cm water-equivalent range shifter (RS) was placed along the beamline to reach shallower penetration depths. In order to achieve steep lateral dose gradients, the position of the RS and patient-specific collimator were simulated using MonteCarlo (MC) FLUKA code. Lateral dose profiles were measured with gafchromic EBT3 films to evaluate lateral penumbra width and dose homogeneity. Several beam scanning patterns were tested. Depth-dose distributions (DDDs) were measured with the Peakfinder system. To obtain uniform dose distributions (Spread-Out Bragg Peaks, SOBPs), the weights of each DDD were optimized simulating different targets. Absorbed doses were then measured in water with an advanced Markus chamber. Neutron dose at the contralateral eye was also evaluated with passive bubble dosimeters. Results: MC simulations and experimental results showed that maximizing the distance between RS and collimator reduces the lateral dose penumbra of the collimated beam and increases field transversal dose homogeneity. Therefore, RS and patient-specific collimator were placed at about 98 cm (behind beam monitors) and 6 cm from the isocenter, respectively. The lateral penumbra (distal fall-off) ranged between 1.0 and 1.8 mm (1.0 and 1.6 mm). The measured SOBP doses were in very good agreement with MC simulations, as shown in Fig. 1. The mean neutron dose at the contralateral eye was 68.8 ± 10.2 μSv/Gy. Conclusions: Our eyeline satisfied the requirements to treat ocular tumors. The first ocular patient was treated in August 2016. Around 60 patients have been treated so far.